The Tragedy of Liberal Democratic Governance in the Face of Global Threats - Muraille, Eric; Naccache, Philippe; Pillot, Julien (Frontiers in Public Health, 2022)
In hindsight, the early response of liberal governments to the SARS-CoV-2 pandemic was chaotic and generally inefficient. Though one might be tempted to attribute these failures to the incompetence of certain political decision-makers, we propose another explanation. Global threats require a coordinated international response, which is only possible if the threat is perceived in the same way by all, and if government priorities are similar. The effectiveness of the response also relies on massive adhesion of citizens to the measures imposed, which in turn requires trust in government. Our hypothesis is that certain fundamental features of liberalism complicate such global and collective responses: neutrality of the state and primacy of the individual over collective society. Liberalism considers that institutions and public policy must not be designed to favor any specific conception of the common good. That which is best for all is usually determined by a “competition of opinions,” which frequently leads to scientific expertise being considered as only one opinion among many. Liberalism also imposes strict respect for individual freedoms and private interests and tends to reject any form of collectivism or dictate imposed by the common good. In order to solve these structural problems and improve society's management of global threats, we make several proposals, such as the introduction of a minimal and consensual definition of the common good and the promotion of a health policy guided by One Health-like concepts. Overall, our analysis suggests that because political ideologies provide their own definitions of the common good and the place of scientific knowledge in the governance process and can thus affect the response to global threats, they should be urgently taken into consideration by public health experts.